The new Asian Active Ageing Index: A case study of gender differences between two ASEAN member countries, Indonesia and Thailand - Asghar Zaidi; Jinpil Um (Asia-Pacific Sustainable Development Journal, 2021)
The speed of population ageing is among the fastest in ASEAN countries. For policy learning, this trend requires a high-quality, independent comparative evidence base. The demographic change has strong implications for sustainable development, especially in the view of the commitment to leave no one behind made in the 2030 Agenda for Sustainable Development. The new Asian Active Ageing Index, which is presented in this paper, quantifies the extent to which older people have been able to and can realize their socioeconomic potential. Using the two most populous member States of ASEAN as examples, Indonesia and Thailand, the Index is sensitized to the Asia-Pacific cultural norms, such as the role of older persons in the society and the informal nature of contributions of older persons to their families and communities.